1969
DOI: 10.1192/bjp.115.520.257
|View full text |Cite
|
Sign up to set email alerts
|

Bi-frontal Stereotactic Tractotomy: An Atraumatic Operation of Value in the Treatment of Intractable Psychoneurosis

Abstract: Stereotactic surgery has provided a means of producing accurate lesions at selected points in the nervous system where concentrations of nerve cells or fibre pathways possessing specific functions permit some small area of anatomical destruction to produce widespread physiological effects. The value of this method in relation to motor and sensory activity is illustrated by the results of thalamotomy in the treatment of Parkinsonian tremor and by stereotactic division of the spinothalamic tract in the cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In SCT bilateral lesions are placed, among other areas, in the substantia innominata of the basal forebrain immediately ventral to the head of the caudate (Knight, 1969). SCT has been used for many decades to treat refractory affective and anxiety disorders, including major depression and OCDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In SCT bilateral lesions are placed, among other areas, in the substantia innominata of the basal forebrain immediately ventral to the head of the caudate (Knight, 1969). SCT has been used for many decades to treat refractory affective and anxiety disorders, including major depression and OCDs.…”
Section: Discussionmentioning
confidence: 99%
“…Various operations specifically designed for the treatment of major depression were developed in the second half of the twentieth century (Richardson, 1973;Knight, 1969;Bailey et al, 1973;Meyerson and Mindus, 1988). Four main lesion sites, alone or in combination, were identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the nucleus accumbens is further stressed by the reports of beneficial effects of subcaudate tractotomy on OCD, anxiety disorders, and depression (Knight, 1969), a bilateral procedure that would interrupt parts of the nucleus accumbens. The finding that, different from the classical bilateral anterior capsulotomy and DBS of the internal capsule in OCD (Meyerson, 1998;Nuttin et al, 1999), right-sided DBS of the nucleus accumbens was sufficient to achieve significant clinical improvement is supported by Lippitz et al (1999) who found right-sided thermo-lesions in the middle part of the anterior limb of the internal capsule to be decisive for a good therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of approach, with minimal disturbance of tissue, ensures that beneficial effects of stereotactic operation are produced in isolation without associated dysfunction of the nervous system. I have shown that this principle can now be applied in relation to the control of emotion (Knight, 1969). Owing to the influence of emotion in depression and psychoneurotic states it is possible to influence many syndromes satisfactorily by operation at a site where connections of primitive cortical areas concerned with instinctive and emotional activity converge beneath the corpus striatum.…”
mentioning
confidence: 99%